Neuroprotective Effect of Daidzein Extracted From Pueraria lobate Radix in a Stroke Model Via the Akt/mTOR/BDNF Channel - Zheng, Meizhu; Zhou, Mi; Chen, Minghui; Lu, Yao; Shi, Dongfang; Wang, Jing; Liu, Chunming (Frontiers in Pharmacology, 2022)
Daidzein is a plant isoflavonoid primarily isolated from Pueraria lobate Radix as the dry root of P. lobata (Willd.) Ohwi, have long been used as nutraceutical and medicinal herb in China. Despite the report on daidzein can prevent neuronal damage and improve outcome in experimental stroke, however, the mechanisms of this neuroprotective action have been not fully elucidated. The aim of this study was to determine whether the daidzein elicits beneficial actions in a stroke model, namely, cerebral ischemia/reperfusion (I/R) injury, and to reveal the underlying neuroprotective mechanisms associated with the regulation of Akt/mTOR/BDNF signal pathway. The results showed that I/R, daidzein treatment significantly improved neurological deficits, infarct volume, and brain edema at 20 and 30mg/kg, respectively. Meanwhile, it was found out that the pretreatment with daidzein at 20 and 30mg/kg evidently improved striatal dopamine and its metabolite levels. In addition, daidzein treatment reduced the cleaved caspase-3 level but enhanced the phosphorylation of Akt, BAD and mTOR. Moreover, daidzein at 30mg/kg treatment enhanced the expression of BDNF and CREB significantly. This protective effect of daidzein was ameliorated by inhibiting the PI3K/Akt/mTOR signaling pathway using LY294002. To sum up, our results demonstrated that daidzein could protect animals against ischemic damage through the regulation of the Akt/mTOR/BDNF channel, and the present study may facilitate the therapeutic research of stroke.